Clinical characteristics and outcomes of people living with HIV hospitalized with COVID-19: a nationwide experience. (April 2021) - Ceballos, Maria Elena; Ross, Patricio; Lasso, Martin; Dominguez, Isabel; Puente, Marcela; Valenzuela, Pablo; Enberg, Margarita; Serri, Michel; Muñoz, Rodrigo; Pinos, Yazmin; Silva, Macarena; Noguera, Matías; et al.
In this prospective, multicentric, observational study, we describe the clinical characteristics and outcomes of people living with HIV (PLHIV) requiring hospitalization due to COVID-19 in Chile and compare them with Chilean general population admitted with SARS-CoV-2. Consecutive PLHIV admitted with COVID-19 in 23 hospitals, between 16 April and 23 June 2020, were included. Data of a temporally matched-hospitalized general population were used to compare demography, comorbidities, COVID-19 symptoms, and major outcomes. In total, 36 PLHIV subjects were enrolled; 92% were male and mean age was 44 years. Most patients (83%) were on antiretroviral therapy; mean CD4 count was 557 cells/mm 3 . Suppressed HIV viremia was found in 68% and 56% had, at least, one comorbidity. Severe COVID-19 occurred in 44.4%, intensive care was required in 22.2%, and five patients died (13.9%). No differences were seen between recovered and deceased patients in CD4 count, HIV viral load, or time since HIV diagnosis. Hypertension and cardiovascular disease were associated with a higher risk of death ( p = 0.02 and 0.006, respectively). Compared with general population, the HIV cohort had significantly more men (OR 0.15; IC 95% 0.07–0.31) and younger age (OR 8.68; IC 95% 2.66–28.31). In PLHIV, we found more intensive care unit admission (OR 2.31; IC 95% 1.05–5.07) but no differences in the need for mechanical ventilation or death. In this cohort of PLHIV hospitalized with COVID-19, hypertension and cardiovascular comorbidities, but not current HIV viro-immunologic status, were the most important risk factors for mortality. No differences were found between PLHIV and general population in the need for mechanical ventilation and death.